SHELL BEADS AS A TOURISM ATTRACTION AT KENJERAN BEACH SURABAYA - Naomi, Laetycia; Shelly Christanti; Nuruddin; Bambang Suharto (Fakultas Pariwisata Universitas Pancasila, 2024)
Tourism is proliferating by becoming the industry that generates the largest revenue in Indonesia. Surabaya is a tourist destination with a maritime concept by exhibiting natural beauty and other supporting attractions in the form of typical souvenirs, namely shell beads. The purpose of the research study of Shell beads as a supporting attraction for tourist attractions at Kenjeran Beach is that this research is expected to positively contribute to the development of tourist attractions at Kenjeran Beach. This research study is associated with previous research specifically that examines beads as a supporting attraction for tourist attractions. The study of research on beads as a supporting attraction in tourist attractions has been done by experts. The results showed that tourists have a positive perception of shell beads as a supporting attraction. Tourists consider the existence of Shell beads not only as souvenirs but as a symbol of local cultural identity that enriches the tourist experience.